Sources of resistance to black aphid in cowpea varieties used as green grains - Borges, Vinicius; Nere, Daniel Rodrigues; da Silva, Leandro Carvalho; Caminha, Marília Gomes; Bleicher, Ervino; Bertini, Cândida Hermínia Campos de Magalhães (EntomoBrasilis, 2020)
Evaluation of resistance of Vigna unguiculata L. landraces, used as green beans, to Aphis craccivora Koch was tested. Eleven landraces and standard genotypes were used in a free choice protocol: BR 17-Gurguéia, VITA 7 (susceptible), BRS Guariba and TVu 408P2 (resistant). A completely randomized blocks design was used with six replicates. Seedlings were infested with five six-day-old adult insects. The number of alive adults after 48 h and of alive nymphs after 96 h was evaluated. The results evidenced that there are high genetic diversity among the landraces, the antibiosis as the main mechanism of resistance. By means of multivariate analysis we suggest crosses among the commercial cultivar BRS Guariba and the most dissimilar varieties CCE-088, CCE-075, CCE-013 and CCE-062 to obtain superior hybrids.